2016
DOI: 10.5713/ajas.16.0009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Salivary Cortisol Concentration in Horses during Different Types of Exercise

Abstract: This study aimed to estimate the change of stress level in horses based on cortisol concentration levels in their saliva. A total of 61 horses were divided into the following three groups: i) tourist riding experience (TR, n = 23); ii) resting group (RR, n = 14); and iii) horse-riding education (ER, n = 24). The saliva samples of TR and ER groups were taken using plain cotton Salivettes four times a day: at 07:00 (basal), 11:00 (Exercise 1, after 1-hour exercise in the morning), 14:00 (Exercise 2, after 1-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…While there is an abundance of literature evaluating serum cortisol levels in horses, salivary cortisol may be a better measure of pain response as it measures the unbound metabolically active portion, as opposed to serum cortisol, which measures both bound and unbound fraction ( 7 ). The salivary cortisol concentrations in our horses were not different due to treatment or over time and cortisol concentrations in both groups (1.4 and 1.7 ng/ml after BMA and SHAM procedures) were below the known resting salivary cortisol concentrations of 2 ng/ml ( 7 , 10 , 13 ). This indicates there was minimal stress or pain response in either group.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…While there is an abundance of literature evaluating serum cortisol levels in horses, salivary cortisol may be a better measure of pain response as it measures the unbound metabolically active portion, as opposed to serum cortisol, which measures both bound and unbound fraction ( 7 ). The salivary cortisol concentrations in our horses were not different due to treatment or over time and cortisol concentrations in both groups (1.4 and 1.7 ng/ml after BMA and SHAM procedures) were below the known resting salivary cortisol concentrations of 2 ng/ml ( 7 , 10 , 13 ). This indicates there was minimal stress or pain response in either group.…”
Section: Discussioncontrasting
confidence: 48%
“…Saliva was collected using a commercially available salivary collection swab (Salivette,® Sarstedt, Germany) that was placed in the buccal space for 1 min as previously described ( 7 , 13 ). Collection swabs were stored at room temperature for 2 h prior to being centrifuged at 1000 g for 2 min and the resulting saliva frozen at −80°C for 30–60 days prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…CORT is frequently used to assess stress levels induced by exercise [70,71]. Different studies have been carried out in relation to stress in horses such as the load stress in tow [61], participation in equestrian dressage competition [72][73][74], competition of resistance [75] jumping [76], tourist driving and education [77]. It has been shown that moderate exercise in horse increases CORT by up to 29% compared to baseline levels through the stress response.…”
Section: Exercisementioning
confidence: 99%
“…Thus, we can state that the values of cortisol in horse saliva are highest in the morning and continually decline over the course of the day and are lowest in the evening/night. Kang and Lee (2016) observed changes in salivary cortisol concentrations in tourist-riding horses, resting group and education horse-riding group of horses. They found out that basal concentrations of cortisol in horse saliva in resting group were 1.113 ng/mL which is in the middle of our measured values.…”
Section: Resultsmentioning
confidence: 82%